BIAN-Fluorene Copolymer Bearing Ruthenium Pendant as Sensitizer of Titanium Nanotubes for Photocatalytic Hydrogen Evolution. Issue 15 (1st January 2018) - Patnaik, S. G.; Gagan, R. K.; Vedarajan, R.; Yamaguchi, A.; Miyauchi, M.; Matsumi, N.
Abstract : We describe ruthenium coordinated n-type polymer material as a sensitizer for TiO2 nanotubes for visible light driven photocatalytic production of hydrogen. The dye is a novel ruthenium coordinated BIAN (bisiminoacenaphthene)-Fluorene (2, 7-Diethynyl-9, 9-dioctyl-9H-fluorene) polymer. Photoresponse of the material was observed by measuring the changes in the open circuit potential voltage which showed a vertical drop of 0.57 V in the potential. From the I-V characteristics, the maximum value of photocurrent observed in the presence of visible light was 245 μA. The monitoring of rate of H2 evolution exhibited as high as 3.75 μmol/hour of H2 with the dye sensitized TiO2 nanotubes at a low bias potential of 0.15V (vs Ag/AgCl), compared to only 2.1 μmol/hour in case of bare TiO2 nanotubes even at higher bias potential of 0.5V. This shows the material has got the potential as a photocatalyst in the photoelectrochemical splitting of water.